Klinik Limbah: Pengolahan Limbah Organik Berbasis 3R di Desa Kasang Pudak Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Monik Kasman; Venny Yusiana; Hadrah Hadrah (Jurnal Daur Lingkungan, 2018)
Kasang Pudak Village is located in Kumpeh Ulu District, directly adjacent to Jambi City. Kumpeh Ulu Subdistrict is developed quite rapidly due to the increasing economic and social activities of the urban community, which also influenced the social life of the city of Jambi. The lack of community awareness of the environment and the unavailability of waste management services and TPA (final processing facility) has an impact on environmental conditions in Kasang Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency. By-products from agricultural activities and the capacity of rural community, especially women (mothers – housewives) who can be empowered, are an extraordinary combination of environmental management. Therefore, there needs to be a conjunction for the community to be more concerned on the environment. This community partnership program (PKM) offers an empowerment of the Kasang Pudak Village community through the establishment of a waste clinic community. The waste clinic is a community development forum that offers training programs, education and providing skills and assistance to residents in environmental management, especially waste. The target partners of this service are mothers - housewives who are members of the Kasang Pudak Village environmental care group. The waste clinic in this PKM provides training in the form of material exposure and skills including the introduction of environmental management, training in composting/ fertilizer making, entrepreneurship training and composting competitions. The long-term outcome of PKM is that the independence of mothers and young women in waste management not only improves the quality of the environment but also economic income. The waste clinic activities were able to increase participant’s knowledge and awareness as indicated by the sincerity of participants in waste sorting and composting. As a result of the interim monitoring, residents succeeded in producing compost from household organic waste, and used it for fertilizer plants.